Institutions of divine and secular learning and On the soul - Cassiodorus, Flavius Magnus Aurelius, asi 490-asi 583 (Translated texts for historians ;, 2004)
As a minister of the Ostrogothic regime in the time of Theoderic, Cassiodorus had as brilliant a political career as any Roman of the late empire. Around 538 CE he published a collection of his state letters under the title of Variae (TTH 12), and disappeared from the public record. Half a century later, dying at his country estate in Calabria, he left behind the exemplars for another world of texts: that of the Christian universe of Scripture, now encompassing the Seven Liberal Arts. The grand plan of this new dispensation is contained in the two books of his Institutions of Divine and Secular Learning, a work which would be excerpted and copied in monasteries throughout the Latin Middle Ages. The Institutions appears here in the first new English translation in more than fifty years. The treatise On the Soul, which was originally published as the thirteenth book of the Variae, is included as an appendix. For a long while mistakenly revered as a saviour of classical civilization, in recent times more often dismissed as an anachronism, Cassiodorus emerges from this edition of the Institutions as an exceptional but nonetheless representative exponent of the learned Christian culture of later Latin Antiquity. The work will be of interest to historians of the late Roman empire and the early Christian church, medievalists, and students of the classical tradition.